2020
DOI: 10.1007/s00701-019-04195-7
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for herniated lumbar disc in private vs public hospitals: A pragmatic comparative effectiveness study

Abstract: Background There is limited evidence on the comparative performance of private and public healthcare. Our aim was to compare outcomes following surgery for lumbar disc herniation (LDH) in private versus public hospitals. Methods Data were obtained from the Norwegian registry for spine surgery. Primary outcome was change in Oswestry disability index (ODI) 1 year after surgery. Secondary endpoints were quality of life (EuroQol EQ-5D), back and leg pain, complications, and duration of surgery and hospital stays. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 23 publications
0
11
0
1
Order By: Relevance
“…NORspine is a comprehensive registry for quality control and research and includes all eight centers performing cervical spine surgery in Norway. 16 , 17 Currently, approximately 81% of patients who undergo surgery in the cervical spine in Norway are included in NORspine. The inclusion rate for DCM surgery is probably higher as these procedures typically are scheduled.…”
Section: Methodsmentioning
confidence: 99%
“…NORspine is a comprehensive registry for quality control and research and includes all eight centers performing cervical spine surgery in Norway. 16 , 17 Currently, approximately 81% of patients who undergo surgery in the cervical spine in Norway are included in NORspine. The inclusion rate for DCM surgery is probably higher as these procedures typically are scheduled.…”
Section: Methodsmentioning
confidence: 99%
“…In Norway, public health insurance is compulsory; thus, no distinction was made between public or private insurance, or between public and private hospitals. A recent study has shown equivalent effectiveness of lumbar disc surgery between the public and private sector [ 21 ]. Patients were also asked if they had a pending or unresolved claim or litigation issue (yes/no) against (1) the Norwegian public welfare agency fund concerning permanent disability pension or (2) a compensation claim against private insurance companies or the public Norwegian System of Compensation to Patients.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, absence of data on privately funded activity is a limitation in our analysis, as the data re ects most but not all activity. For some of the studied procedures, private activity has been reported to increase variation (3,11). Further, the number of hospitals is a crude measure, as it does not account for differences in hospital capacity.…”
Section: Strengths and Limitationsmentioning
confidence: 98%
“…These hospitals do not report activity data to the national registry. The quality of treatment is considered equivalent in public and private hospitals, and the presumption is backed by a recent study showing equivalent effectiveness of spine surgery in public and private hospitals (11).…”
Section: Settingmentioning
confidence: 99%